"For a witch cannot cross such a threshold!” – Building concealment traditions in Finland c. 1200–1950 - Hukantaival, Sonja (Suomen keskiajan arkeologian seura, 2016)
The study discusses objects deliberately concealed in buildings in Finland during its historical period (c. 1200–1950 CE). The phenomenon is connected with folk religion and especially with a need to protect the household from outside malicious effects. The goals are, first, to map the phenomenon of ritual building concealments in order to discover its extent, manifestations, and possible regional and chronological variations. The more specific hermeneutic aim is to discuss the motives, meanings, and internal logic of the concealments, as well as possible changes in their meanings. The concealment tradition is also studied in its wider contexts of society and worldview. One special aim, from the viewpoint of archaeology, is to introduce a theoretical framework and develop a contextual multi-source method suitable for studying historical folk religion as part of the archaeology of religion. There are two main types of source material in the study: the finds of concealed objects (234) and folklore accounts (775). A few records from witchcraft trials (7) give additional insight to the practices. The folklore depicts concealment traditions known in the 19th century and the early 20th century. This source material also illuminates meanings and motives of the custom, and the relationship between meanings, concealed objects, and their location. Moreover, the folklore shows signs of regional variation between western and eastern Finnish areas. The finds of concealed objects give historical dimension to the practices. They also enable discussing concealment as factual practice. The early modern trial records bring extra information on meanings in times before the folklore was collected. The methodology used in the study is developed on the basis of contextual archaeology and the direct historical approach. Contextual archaeology aims to identify meanings by analysing patterns in the material culture data. The direct historical approach begins its analysis in a well-recorded historical period to which observed changes and continuity is compared when studying preceding periods. In the study at hand contextuality is extended to include the wider context of folk religion and society. The study shows that in densely laid out villages and towns concealing has especially been connected with tensions in social relations caused by uneven distribution of wealth. This is observable in the emphasis on fear of witchcraft practiced by envious neighbours. In more loosely laid out settlements social pressure is less obvious in the concealment practices. Instead, keeping the building lucky and free of pests are more common motives. The regional variation manifests in different emphasis on concealment types, thus completely different traditions are not in question. It is more difficult to observe chronological variation due to the scarce data. It is possible that medieval concealment traditions have been similar to the late modern eastern tradition, where social pressure was not emphasized. Social pressure is still likely to have had a role in medieval towns. New objects for concealing were adopted in new periods; for example concealing mercury is likely to have become common in early or late modern times when the substance became easier to obtain. From the perspective of the archaeology of folk religion, the fact that practices of folk religion leaves traces in the material record is notable. Understanding these contributes to a wider understanding of past human life.

Rakennuskätköperinteet Suomessa n. 1200–1950 Tutkimus käsittelee Suomen alueella historiallisena aikana (n. 1200–1950) rakennuksiin tarkoituksellisesti kätkettyjä esineitä. Ilmiö liittyy kansanuskon kenttään ja erityisesti tarpeeseen suojella kotitaloutta ulkoapäin tulevilta pahoilta vaikutuksilta. Tavoitteina on ensinnä kartoittaa ilmiön laajuus ja muodot. Varsinainen päätavoite on selvittää kätköperinteen merkityksiä, merkitysten muutoksia ja erityisesti ilmiön sijoittumista laajempaan yhteyteensä yhteiskunnassa. Arkeologian kannalta erityisenä tavoitteena on esitellä kansanuskon materiaalisen kulttuurin tutkimukseen soveltuvaa teoreettista viitekehystä ja kehittää moniaineistoista metodologiaa. Tutkimusaineisto koostuu kahdesta pääaineistosta: varsinaiset kätkölöydöt (234 kpl) ja folklore-tiedonannot (775 kpl). Näiden lisäksi tutkimuksessa hyödynnetään muutamia noituus- ja taikuusoikeu-denkäyntien pöytäkirjoja (7 kpl). Folklore-tiedonannot kuvaavat kätköperinteitä 1800-luvun loppupuolella ja 1900-luvun alussa. Tämä aineisto avaa myös perinteeseen liittyneitä merkityksiä ja näiden merkitysten suhdetta kätköobjektiin ja kätköpaikkaan. Tässä aineistossa on myös havaittavissa alueellisia eroja länsi-suomalaisen ja itäsuomalaisen kulttuurialueen välillä. Kätkölöydöt sitovat käytänteet omaan aikaansa. Lisäksi löydöt mahdollistavat kätkötapojen tarkastelun tosiasiallisesti suoritettuina rituaaleina. Uuden ajan oikeudenkäyntiaineistot tuovat lisänäkökulman folklorea varhaisempiin merkityssisältöihin. Aineistoa käsitellään metodilla, joka on kehitelty kontekstuaalisen arkeologian ja historiallisen jatkuvuuden lähestymistavan pohjalta. Kontekstuaalinen arkeologia pyrkii tunnistamaan merkityssisältöjä analysoimalla materiaalisessa kulttuurissa havaittavia kuvioita, eroja ja yhtäläisyyksiä. Historiallisen jatkuvuuden lähestymistavassa puolestaan ilmiön tarkastelu aloitetaan hyvin dokumentoidusta ajankohdasta, josta lähdetään seuraamaan ilmiön muutoksia ja pysyvyyttä ajassa taaksepäin liikuttaessa. Tutkimuksessa kontekstuaalisuus on ulotettu myös kattamaan ilmiön sijoittumista kansanuskoon ja yhteiskuntaan laajemmin. Tutkimuksessa käy ilmi, että tiiviimmin asutuissa kylissä ja kaupungeissa kätkeminen on erityisesti liittynyt sosiaalisissa suhteissa oleviin jännitteisiin, jotka liittyvät varallisuuseroihin. Tämä näkyy kateellisten naapureiden aiheuttaman noituuden korostumisena erityisenä huolenaiheena. Väljemmin asutuilla alueilla sosiaalinen paine on vähäisempi kätkösyy, sen sijaan rakennuksen pitäminen onnellisena ja puhtaana syöpäläisistä ovat merkittäviä syitä. Alueelliset erot näkyvät eri kätköperinteiden välisen suhteen vaihteluna, eli täysin erilaisista perinteistä ei ole kyse. Ajallisia muutoksia on vaikeampi havaita niukemman aineiston takia. On kuitenkin mahdollista, että keskiaikaiset kätköt ovat laajemmilla alueilla muistuttaneet itäisillä kulttuurialueilla havaittavia muotoja, joissa sosiaalinen paine ei korostu. Tämä paine on silti todennäköinen kätkösyy keskiaikaisissa kaupungeissa ja ryhmäkylissä. Eri aikakausina kätköperinteeseen on omaksuttu uusia kätköobjekteja, esimerkiksi uudella tai uusimmalla ajalla elohopean kätkeminen on todennäköisesti yleistynyt, aineen saannin helpotuttua. Kansanuskon arkeologian tutkimuksen kannalta on huomattavaa kansanuskon piiriin kuuluvien tapojen ja uskomusten jälkien jääminen arkeologiseen aineistoon ja näiden ymmärtämisen vaikutus laajempaan ihmisyhteisöjen ymmärtämiseen.